Ethical, clinical and technical analysis of face transplantation - Lourenço, Matheus França; Anton, Juliana Maria; Fujii, Larissa Izumi; Laranjeira, Isabela Ormond Cesar; Falarini, Julia; Granja, Aline Cristina Ormond; Ormond, Débora Teresa da Silva; Bezerra, Cícero Dayves da Silva; Hojaij, Flávio Carneiro (Journal of Oral Diagnosis, 2020)
Introduction: Face transplants constitute a new reality in reconstructive surgery, allowing a new perspective on the restoration of complex facial defects and the possible complications resulting from this procedure. Methods: The purpose of this work is to perform a bibliographic review on the techniques used to perform face transplantation, their difficulties of execution, possible post-operative clinical repercussions and the bioethics of face transplantation. Results: Since 2005 more than 30 face transplants have been performed in the world, the patients submitted to this procedure showed a good sensory recovery, successful motor and functional recovery slower and variable. Regarding the aesthetic and psychological issues, all patients have reported improvements. However, acute rejection is common to solid organ transplants and allograft, while chronic rejection has not been reported in even one face transplant case. Discussion: One of the controversial aspects of face transplantation is that it is a high-risk procedure for a non-life threatening condition; lifelong use of immunosuppressants; and complications affecting the individual after transplantation. Conclusion: Therefore, face transplantation presents itself as a therapeutic option, which applies to a very limited number of patients, in which conventional reconstructive techniques have not been successful, which have brought functional, psychological and social comorbidities to the transplanted patient.